Chinese enterprise, transnationalism, and identity - Gomez, Edmund Terence; Xiao, Xinhuang (Chinese worlds., 2004)
The book examines the variety of issues surrounding Chinese enterprise development from national and transnational perspectives, starting with the role played by Chinese entrepreneurs in the 1997 Asian financial crisis.